Principal Construction of Normative Frameworks: Improving Schooling for Students - John L. Keedy; David S. Seeley; Paul F. Bitting (Educational Considerations, 1995)
Unless leadership candidates develop different normative frameworks on which they can ground their decisions, how can we expect schools to be different?